APE UNTUK PENGEMBANGAN NILAI AGAMA DAN MORAL ANAK - Utami Budiyati (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Keagamaan Islam UNUGHA Cilacap, 2021)
This study uses the library research method, researchers seek information about APE and the development of children's religious and moral values ​​from various literacy sources. In addition to books and journals, the author also gets from other literacy sources. APE for the development of religious and moral values ​​that are suitable for ages 3-6 years / phase of The Fairy Stage (Fairy Tale Level); a. Islamic fairy tale books, b. Islamic finger puppets, c. Diorama of daily activities and prayers, d. Cards with pictures of daily activities and prayers, e. Mind mapping of pious/sholihah children, f. Hijaiyyah letter trains, g. Mystery Box and Ball, h. Hijaiyyah Fruit, i. Making miniature prayer rugs, j. Puzzle with pictures of praying, doing ablution, giving alms, sweeping the floor, taking care of younger siblings, hijaiyyah letters.